A CROSS-SECTIONAL MORPHOMETRIC ANALYSIS OF THE PROXIMAL FEMUR IN THE INDIAN POPULATION: IMPLICATIONS FOR TOTAL HIP ARTHROPLASTY - Mishra, Gopabandhu; Dash, Lipsita; Sahoo, Duryodhan (Student's Journal of Health Research Africa, 2024)
Background Total hip arthroplasty (THA) is one of the most popular orthopedic operations in the world. Implant design and surgical outcome are greatly influenced by the proximal femur's anatomy. Morphometric variations between populations necessitate region-specific data to ensure optimal outcomes. The study assessed the morphology of the proximal femur in dry human cadaveric bones, which has potential implications for THA. Methods 110 dry cadaveric femur bones of unknown age and sex were analyzed. Parameters such as femur length (FL), femoral head diameter (FHD), femoral neck length (FNL), femoral neck width (FNW), neck-shaft angle (NSA), and the length of the intertrochanteric line were measured using digital calipers, goniometers, and osteometric boards. Descriptive statistics were applied, and comparisons with global populations were made using the Unpaired Student's t-test. Results The mean femur length was 427.56 mm, shorter than the global average. Statistically significant variations (p < 0.05) were observed in FL, FNL, and NSA when compared to global populations. Significant correlations were also identified between femur length and femoral head diameter (r = 0.48) and between femur length and neck-shaft angle (r = -0.42). Conclusion The study highlights significant morphological differences in the proximal femur of the Indian population compared to global populations, indicating the necessity for region-specific prosthetic designs. Standard implants may not provide an optimal fit for Indian patients, leading to potential complications. Recommendations Further research is recommended to develop customized prostheses tailored to the Indian population’s anatomical variations. This would enhance THA outcomes and reduce the risk of post-operative complications.